A retrospective study of unerupted maxillary incisors associated with supernumerary teeth - C. Mason,* N. Azam, R.D. Holt, D.C. Rule (Blackwell Synergy, 2000)
Supernumerary teeth are those that are additional to the normal complement. They may develop in any region of the dental arch, but are most common in the anterior maxilla. The quoted incidence varies depending on whether or not radiographs have been taken. In the primary dentition, the incidence is said to be 0.3%–0.8% and in the permanent dentition 1.5%–3.5%, with a male:female ratio of 2:1. Supernumerary teeth are more common among Mongoloid racial groups, patients with cleft lip and palate, and those with cleidocranial dysplasia.